EVALUATION OF THE DETERMINATION OF THE CHROMOGRANIN MARKER AS AN ADDITIONAL DIAGNOSTIC SIGN OF VARIOUS VARIANTS OF ESOPHAGEAL ATRESIA IN NEWBORNS - Erkin A. Eshbaev; Aziz A. Zufarov; Makhzuna Kh. Mukhsinova (Central Asian Journal of Medicine, 2025)
When studying the immunohistochemical aspects of various clinical and morphological types of atresia, which is one of the developmental anomalies of the esophagus, the Chromogranin marker is used to identify secretory neurons that mark the neuromuscular synapses of neuroendocrine cells and to determine whether the synthesis of functional peptide bonds occurs. By its nature it is a glycoprotein marker, which makes it possible to assess the morphofunctional state by staining the vesicles of neuromuscular synapses in the muscle layer. The high sensitivity of this marker in very low titers demonstrates all the symptoms of APUD cells masking vesicles in neuromuscular synapses. This makes it possible to plan treatment based on important criteria for determining the treatment tactics for various types of esophageal atresia.